Bivalves and microbes: a mini-review of their relationship and potential implications for human health in a rapidly warming ocean - Masanja, Fortunatus; Yang, Ke; Xu, Yang; He, Guixiang; Liu, Xiaolong; Xu, Xin; Jiang, Xiaoyan; Luo, Xin; Mkuye, Robert; Deng, Yuewen; Zhao, Liqiang (Frontiers in Marine Science, 2023)
Heatwaves have become increasingly frequent and intense, posing a significant threat to the survival and health of marine bivalves. The temperature fluctuations associated with heatwaves can cause significant alterations in the composition and quantity of microbial communities in bivalves, resulting in changes to their immunological responses, gut microbiome, oxidative stress levels, and other physiological processes and eventually making them more susceptible to diseases and mass mortalities. This is particularly concerning because some of these bivalves are consumed raw, which could represent a risk to human health. This paper provides an overview of the current state of knowledge regarding the impact of marine heatwaves on bivalves and their microbial communities, demonstrating the intricate relationship between heatwaves, microbial ecosystems, and bivalve health. Our analysis highlights the need for additional research to establish the underlying mechanisms of these reactions and to develop appropriate conservation and management strategies to limit the impact of heatwaves on bivalves and their microbial ecosystems.